Terms of Trade Shocks and the Current Account - Cashin, Paul (IMF Working Papers; Working Paper, 1998)
This paper examines the relationship between terms of trade shocks, private saving, and the current account position. The relationship between these variables is theoretically ambiguous: an adverse transitory terms of trade shock can either induce a deterioration or an improvement in the current account, depending on whether the resulting income effects are greater or less than the resulting substitution effects. The substitution effects involve both intertemporally substituting consumption and intratemporally substituting consumption between importables and nontradables. The relative strength of these substitution effects is estimated using data for five OECD countries during 1970/95; both are found to exert large and significant effects on the current account balance.